ANALISA PENGGUNAAN LAMPU SPOT LIGHT PADA PAGELARAN SENDRATARI MAHABRATA GUGURNYA BISMA DI OPEN STAGE, ART CENTRE, WERDI BUDAYA, DENPASAR, BALI - Abdul Hakim; Purwanto; Aprilina Dwi Astuti (HERITAGE, 2023)
ABSTRACT: The series of Bali Arts Festival (PKB) activities are activities that the Balinese people have been waiting for, one of which is the Sendatari Performance which takes place on the open stage, Werdi Budaya, Art Center, Denpasar, Bali. The Mahabrata Ballet episode of the Fall of Bhishma which takes place on the open stage at the Art Center can be watched by the public directly at the location and broadcast live by the local television broadcaster TVRI Bali Station. The performance takes place at night so lighting is a very important factor in supporting the performance. With the correct placement of the lights, a clear image will be produced so that it can be viewed comfortably by viewers at home. The aim of the research is to analyze the types of lights and their placement in ballet performances. This research uses a qualitative research method by analyzing the data descriptively. The analysis was carried out via YouTube media on the Nurai Production Channel link with the content of the Mahabrata Ballet episode, The Fall of Bhishma, specifically regarding the use of lighting, including the types of lights used in the performance. The results of this research were that the lighting used utilized several types of spot lights, with 16 tungsten light units. The lights are directed to several areas, including the ballet area in the middle of the open stage as the main area, the area for traditional musical instruments and stringers, the audience and VIP areas as well as the building part of the open stage